The Implementation of Personnel Management to Produce Good Quality of Education - nor syahid; Hanif Mubarok (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2017)
The purpose of this research is to: 1) To describe the implementation of personnel management to produce good quality of education at SMK PGRI 2 Ponorogo. 2) to describe the quality of education at SMK PGRI 2 ponorogo. 3) To describe the supporting and obstacle factors in implementation of personnel management at SMK PGRI 2 Ponorogo. This study uses qualitative methods through field research. In collecting the data, researchers using three methods, interview method, observation method, and documentation method. In analizing data, researchers use model analysis of Miles & Huberman,namely, data reduction, data display, and verification.The results of this study are: 1) Personel management at SMK PGRI 2 Ponorogo has been managed as well as possible through, personnel planning, personnel recruitment, personnel selection, personnel appointment, personnel palcement, personnel maintenances, personnel developemnt, personnel termination, personnel termination, and personnel approach. 2) A good education quality standards based vocational education in this school are: many graduates are absorbed in the industrialized world, educators or instructors have successful experience in the application of skills and knowledge, school environment are replica of industry, practical tools standarised by industrial world, many in cooperation with the industrial world, as well as the performance of graduates in accordance with the expectations of the industry. 3) The supporting factors in implementation of personnel management at SMK PGRI 2 Ponorogo is: teachers placement adjusted with the competencies, teachers are given freedom to improve their quality, the harmonious school environment, practical tools standarised by indutrial world, teacher’s welfared is guaranteed. While the obstacle factor is: gain training and developmen that have ever been held before, a broken practice tools when teaching and learning activities, and the presence of teacher who are less able to manage class well.